Cyanide and the human brain: perspectives from a model of food (cassava) poisoning. Issue 1 (23rd July 2016) - Tshala‐Katumbay, Desire D.; Ngombe, Nadege N.; Okitundu, Daniel; David, Larry; Westaway, Shawn K.; Boivin, Michael J.; Mumba, Ngoyi D.; Banea, Jean‐Pierre
Abstract : Threats by fundamentalist leaders to use chemical weapons have resulted in renewed interest in cyanide toxicity. Relevant insights may be gained from studies on cyanide mass intoxication in populations relying on cyanogenic cassava as the main source of food. In these populations, sublethal concentrations (up to 80 μmol/l) of cyanide in the blood are commonplace and lead to signs of acute toxicity. Long‐term toxicity signs include a distinct and irreversible spastic paralysis, known as konzo, and cognition deficits, mainly in sequential processing (visual–spatial analysis) domains. Toxic culprits include cyanide (mitochondrial toxicant), thiocyanate (AMPA‐receptor chaotropic cyanide metabolite), cyanate (protein‐carbamoylating cyanide metabolite), and 2‐iminothiazolidine‐4‐carboxylic acid (seizure inducer). Factors of susceptibility include younger age, female gender, protein‐deficient diet, and, possibly, the gut functional metagenome. The existence of uniquely exposed and neurologically affected populations offers invaluable research opportunities to develop a comprehensive understanding of cyanide toxicity and test or validate point‐of‐care diagnostic tools and treatment options to be included in preparedness kits in response to cyanide‐related threats.